Antioxidant activity of phenolic compound of Astraeus hygrometricus: A Case of Ranchi, India - Foziya Khan; Ramesh Chandra (Universitas Gadjah Mada, 2022)
The forest region of Ranchi district of Jharkhand, India, is very rich with different types of wild mushrooms. This study collected two hundred samples. There are nine different species were identifiedand one them was Astraeus hygrometricus that chosen for isolation, purification, and characterization of its compounds. This mushroom was chosen because of its nutritive value as for human consumption and also fewer studies done on it. It has got many compounds unrevealed. Various techniques such as solvent extraction including phase separation, TLC, FT-IR, and MS were employed in this study. Also, the total phenol content and antioxidant assay (DPPH) of the purified transparent compound of methanolic extract was carried out. The study showed that unknown transparent phenolic compound, established as astrakurkurol with molecular weight 485 was obtained.